The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1037/h0080330
|View full text |Cite
|
Sign up to set email alerts
|

Assertive community treatment for patients with co-occurring severe mental illness and substance use disorder: A clinical trial.

Abstract: Integrated mental health and substance abuse treatment within an assertive community treatment (ACT) approach was compared to that within a standard case management approach for 223 patients with dual disorders over three years. ACT patients showed greater improvements on some measures of substance abuse and quality of life, but the groups were equivalent on most measures, including stable community days, hospital days, psychiatric symptoms, and remission of substance use disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
233
1
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 372 publications
(249 citation statements)
references
References 68 publications
11
233
1
4
Order By: Relevance
“…Similar results were published in the US also although less commented upon (e.g. Drake et al, 1998). The two most influential of these European studies were the PRiSM study at the Maudsley Hospital in London (Thornicroft et al, 1998) and the multi-centre UK700 trial (Burns et al, 1999).…”
Section: The Fading Of Act Superioritysupporting
confidence: 71%
“…Similar results were published in the US also although less commented upon (e.g. Drake et al, 1998). The two most influential of these European studies were the PRiSM study at the Maudsley Hospital in London (Thornicroft et al, 1998) and the multi-centre UK700 trial (Burns et al, 1999).…”
Section: The Fading Of Act Superioritysupporting
confidence: 71%
“…This finding is consistent with the work of Drake et al 22 , and others using long-term models, but is in stark contrast to the findings of Havassy, et al 23 who observed that intensive and expanded brokerage case management were largely ineffective for decreasing hospitalizations among dually diagnosed subjects. It is possible that TLC was successful in reducing re-hospitalization because the program's staff directly addressed the challenges associated with co-morbid disorders through DRT in addition to offering case management services.…”
Section: A Brief Community Linkage Intervention 149contrasting
confidence: 57%
“…Important adaptations exist for using ACT with special problem populations such as people with severe mental illness who are also dually diagnosed with substance abuse [37] and/or early psychosis [38], are homeless [39][40], or have brain or sensory impairment, e.g., deafness. However, insufficient research supports their effectiveness as yet [18].…”
Section: Special Populations and Needsmentioning
confidence: 99%